Pengaruh Penggunaan Polard Sebagai Aditif Terhadap Karakteristik Fisik Silase Limbah Sayur Kubis - Nurianti Christin Missa; Edwin J.L Lazarus; Emma D. Wie Lawa (Lembaga Bale Literasi, 2025)
This study aims to evaluate the physical characteristics of cabbage (Brassica oleracea) vegetable waste silage due to the use of pollard as an additive. This study used an experimental method and was designed using a completely randomized design (CRD) with 4 treatments and 4 replicates. The treatments were P0= Cabbage vegetable waste without pollard, P1= Cabbage vegetable waste + 3% pollard, P2: Cabbage vegetable waste + 6% pollard, P3: Cabbage vegetable waste + pollard 9%. Physical characteristics variables measured were color, texture, aroma, mold, and pH. Physical characteristics were observed using organoleptic test score instructions from 15 panelists. Data were analyzed using Kruskal-Wallis Analysis followed by Mann-Whitney. The pH value was measured using a pH meter and the data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test. The results showed that the use of pollard had a significant effect (P0.05). It was concluded that the use of pollard bran in making cabbage vegetable waste silage (Brassica oleracea) produces a good effect on the physical characteristics of cabbage vegetable waste silage and the best level of pollard bran use as an additive is 9%.